ANALISIS PERLINDUNGAN HUKUM DAN KEBIJAKAN PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENCURIAN YANG DIPICU OLEH KETIDAKSTABILAN EKONOMI: PERSPEKTIF KEADILAN RESTORATIF DALAM SISTEM HUKUM PIDANA INDONESIA - Muhammad Gazali Rahman; Al-Amin (CV. Adiba Aisha Amira, 2025)
Economic instability is often a factor that triggers an increase in theft crimes, especially among economically disadvantaged communities who are driven by the need to survive. This phenomenon raises serious issues in Indonesia's criminal justice system, as it demonstrates the link between socio-economic conditions and criminal behaviour motivated by structural pressures. This study aims to analyse the forms of legal protection for perpetrators and victims of theft triggered by unstable economic conditions, as well as to examine ideal law enforcement policies based on the principles of restorative justice. Through a normative juridical approach supported by empirical data, this study examines relevant legislation, progressive legal theory, and the practice of implementing restorative justice in Indonesia. The results of the analysis show that current legal protection is still formalistic and does not fully consider the socio-economic background of perpetrators as part of substantive justice considerations. The retributive approach, which emphasises prison sentences, has limitations in terms of social recovery and recidivism prevention. In contrast, the restorative justice model provides a more humane alternative to resolving cases by focusing on the perpetrator's responsibility, compensation for the victim's losses, and social reconciliation. Criminal justice policies based on the restorative paradigm are believed to increase the effectiveness of law enforcement, strengthen public trust in law enforcement agencies, and broaden the meaning of justice for economically disadvantaged communities. This study concludes that the application of restorative justice in handling criminal acts of theft due to economic instability is an important step in reforming Indonesia's criminal justice system. This concept is in line with the values of Pancasila, the principles of humanity, and social justice, which are the foundations of the state. To be effective, its implementation needs to be accompanied by the development of law enforcement officials, regulatory reform, and increased public awareness of the importance of legal resolutions that are oriented towards restoration and social balance.